LIGHT AMPLIFICATION BASED ON ELECTROMAGNETICALLY INDUCED TRANSPARENCY IN A THREE-LEVEL V-TYPE ATOMIC SYSTEM - Lê Văn Đoài; Võ Bá Tòng (Tạp chí Khoa học Đại học Đà Lạt)
Electromagnetically induced transparency (EIT), which was discovered in the past few decades, leads to an elimination of the absorption coefficient in an atomic medium and is fundamental to create light amplification without inversion. In this paper, we study light amplification without inversion in a three-level V-type atomic system via the EIT effect. By solving the density matrix equations, we found the expressions for absorption, dispersion, and amplification coefficients of probe light according to the parameters of the coupling light. We found the frequency region in which the probe light is amplified without inversion. This frequency region can also be shifted to either the short or long wavelength region by changing the coupling light frequency.